Clinical manifestations in patients with PI*MMMalton genotypes. A matter still unsolved in alpha‐1 antitrypsin deficiency - Marina Aiello; Alberto Fantin; Chiara Longo; Ilaria Ferrarotti; Giuseppina Bertorelli; Alfredo Chetta (Respirology Case Reports, 2020)
We report the genetic variants associated with alpha‐1 antitrypsin deficiency (AATD) in 117 patients admitted to our outpatient clinic and characterized by a serum concentration of AAT lower than 113 mg/dL. We focused on the M‐like heterozygous variant of the SERPINA1 gene called PI*MMMalton, and describe three patients with this variant. While the role of homozygous AATD in liver and pulmonary disease is well established, the association between heterozygous AATD and chronic liver and pulmonary disease is still under investigation. The PI*MMMalton genotype was found in 5.8% of patients with a pathological genotype of AATD and in 14.3% of the subjects when considering only those with intermediate AATD. There were no liver or renal abnormalities in patients with the PI*MMMalton genotype. The PI*MMMalton patients included here showed a normal liver function, and none had renal function abnormalities or abdominal aortic aneurysm. Only a prevalence of lung disease was detected.